2023
DOI: 10.4028/p-2j4d93
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment and Treatment of Dredged Sediments and Limestone Tuff Using Waste Ceramic with Low-Cement

Abstract: Dredged sediments are a valuable natural resource used in construction and public works, however some dredged sediments do not have the physical and chemical qualities necessary for reuse, necessitating the addition of complementary materials such as ceramic waste powder. The main objective of this study is to improve the technical quality of sediments by adding ceramic waste powder and cement in low content by strengthening its mechanical and geotechnical properties. The present paper reports the treatment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The dry density values decrease as the plastic powder values increase, and the decrease is more remarkable as the plastic powder content values reach higher values. This can be attributed to a change in the partial composition of the mixture (incompatibility of expansive soil particles with plastic powder).Several authors have reported these results using rubber or plastic of similar physical composition [18], and concluded that the optimal water content remains constant and that the percentage decrease in maximum dry density exceeds 10.6% when the powder is used. The percentage exceeds plastic-supported by granite powder by 2%.…”
Section: Maximum Dry Density (Mdd)mentioning
confidence: 98%
“…The dry density values decrease as the plastic powder values increase, and the decrease is more remarkable as the plastic powder content values reach higher values. This can be attributed to a change in the partial composition of the mixture (incompatibility of expansive soil particles with plastic powder).Several authors have reported these results using rubber or plastic of similar physical composition [18], and concluded that the optimal water content remains constant and that the percentage decrease in maximum dry density exceeds 10.6% when the powder is used. The percentage exceeds plastic-supported by granite powder by 2%.…”
Section: Maximum Dry Density (Mdd)mentioning
confidence: 98%